Diacylglycerol acyltransferase 1 inhibition with AZD7687 alters lipid handling and hormone secretion in the gut with intolerable side effects: a randomized clinical trial. Issue 4 (31st October 2013) - Denison, H.; Nilsson, C.; Löfgren, L.; Himmelmann, A.; Mårtensson, G.; Knutsson, M.; AL‐Shurbaji, A.; Tornqvist, H.; Eriksson, J. W.
Abstract Aim Inhibition of diacylglycerol acyltransferase 1 (DGAT1) is a potential treatment modality for patients with type 2 diabetes mellitus and obesity, based on preclinical data suggesting it is associated with insulin sensitization and weight loss. This randomized, placebo‐controlled, phase 1 study in 62 overweight or obese men explored the effects and tolerability of AZD7687, a reversible and selective DGAT1 inhibitor. Methods Multiple doses of AZD7687 (1, 2.5, 5, 10 and 20 mg/day, n = 6 or n = 12 for each) or placebo (n = 20) were administered for 1 week. Postprandial serum triacylglycerol (TAG) was measured for 8 h after a standardized 45% fat meal. Glucagon‐like peptide‐1 (GLP‐1) and peptide YY (PYY) were measured and a paracetamol challenge was performed to assess gastric emptying. Results Dose‐dependent reductions in postprandial serum TAG were demonstrated with AZD7687 doses ≥5 mg compared with placebo (p < 0.01). Significant (p < 0.001) increases in plasma GLP‐1 and PYY levels were seen at these doses, but no clear effect on gastric emptying was demonstrated at the end of treatment. With AZD7687 doses >5 mg/day, gastrointestinal (GI) side effects increased; 11/18 of these participants discontinued treatment owing to diarrhoea. Conclusions Altered lipid handling and hormone secretion in the gut were demonstrated during 1‐week treatment with the DGAT1 inhibitor AZD7687. However, the apparent lack of therapeutic window owing to GI side effects of AZD7687, particularly diarrhoea, makes the utility of DGAT1 inhibition as a novel treatment for diabetes and obesity questionable.